2023
DOI: 10.1039/d3su00191a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, biocompatibility, and antimicrobial properties of glucose-based ionic liquids

Abstract: New carbohydrate-based ionic liquids are characterized, towards their thermal stability, biocompatibility and antimicrobial behavior. The results led to structure–property relationships and higher cell viabilities than most commercial ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The first step of this work was to produce the envisioned starting material 3 needed for the hydrogel synthesis. We adopted the reaction conditions from our previous works on glucosyl imidazolium salts bearing different alkyl chain lengths on the imidazole, , this time however focusing on vinyl imidazole (Scheme ). Here, the vinyl group is crucial for the three-dimensional cross-linking of the resulting monomer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first step of this work was to produce the envisioned starting material 3 needed for the hydrogel synthesis. We adopted the reaction conditions from our previous works on glucosyl imidazolium salts bearing different alkyl chain lengths on the imidazole, , this time however focusing on vinyl imidazole (Scheme ). Here, the vinyl group is crucial for the three-dimensional cross-linking of the resulting monomer.…”
Section: Resultsmentioning
confidence: 99%
“…Our group works in the field of carbohydrate-based ionic liquids. We previously found that glucosyl imidazolium-based ionic liquids can be produced in high total yields up to 90% and that they exhibit a remarkably high biocompatibility in comparison to commercial imidazolium ILs . In this work, we synthesized a series of novel glucosyl vinyl imidazolium salts and used these as monomers to produce novel glucose-based ionic hydrogels, cross-linked by several commercially available cross-linkers (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis was carried out as previously reported in our group. [12] In short, methyl-α-D-glucopyranoside was converted into Methyl-6-iodo-α-D-glucopyranoside via a selective Appel-type iodination, followed by the quarternisation with N-methylimidazole in the second step.…”
Section: Synthesis Of 1-(methyl-α-d-glucopyranosid-6-yl)-3methylimida...mentioning
confidence: 99%
“…GMIMÀ I itself can easily be prepared in a two-step synthesis in a total yield of 90 % and has been proven to exhibit a considerably higher biocompatibility than commercially available ILs. [12] Carbohydrate based ILs are not limited to glucose-based compounds. This vast area is covered by extensive reviews recommended to interested readers.…”
Section: Introductionmentioning
confidence: 99%